Red Wine Inspired Chemistry: Hemisynthesis of Procyanidin Analogs and Determination of Their Protein Precipitation Capacity, Octanol-Water Partition, and Stability in Phosphate-Buffered Saline - Laitila Juuso Erik; Tähtinen Petri Tapani; Karonen Maarit; Salminen Juha-Pekka (American Chemical Society, 2025)
Ten dimeric procyanidin (PC) analogs were hemisynthesized from catechin or epicatechin and from five different aldehydes using the same mechanism that produces the important acetaldehyde-mediated adducts of proanthocyanidins (PAs) and anthocyanins in red wine. Protein precipitation capacity (PPC), octanol–water partition coefficient (log P) and stability of the PC analogs were determined. The emphasis was on the PPC because it has been shown to correlate with anthelmintic activity against gastrointestinal nematodes in ruminants and with other beneficial bioactivities in animals, as well. The PPC of PC analogs was greatly improved compared to natural PC dimers, but the capacity was not as great as that of a PC trimer or epigallocatechin gallate. The log P of PC analogs varied from hydrophobic to hydrophilic depending on the intramolecular linkage. Great variation was observed in stabilities of PC analogs in phosphate buffered saline, and the mixtures of degradation products were characterized using high-resolution mass spectrometry.